Наследна тромбофилија кај неповолен исход на бременоста, инфертилитет и неуспешна ин витро фертилизација - Петковиќ, Елена (Медицински факултет, УКИМ, Скопје, 2020)
Background: Thrombophilia is a condition of congenital or acquired predisposition to venous or arterial thromboembolism. There is increasing evidence of association between thrombophilia and adverse pregnancy outcome, infertility and in vitro fertilization (IVF) failure. Aim: of the study is to examine the prvalence and association between inherited thrombophilia and adverse pregnancy outcome, infertility and IVF failure in patients at the Institute of Transfusion Medicine – Skopje. Patients and methods: A total of 151 women were included in a retrospective-prospective case - control study, 115 of them were divided into three groups and 36 women in the control group. The first group included women with a history of adverse pregnancy outcome: missed abortion, blighted ovum, misscarriage in the first or second trimester, fetal loss in a previous pregnancy. The second group included women with primary and secondary infertility. The third group included women with three or more failed cycles of IVF. The control group included women at the same age, who have already given birth, without obstetric complications, at least one healthy child, ie with normal pregnancy outcome. The women have been tested for the presence of gene mutation of factor II (G20210A), factor V Leiden (FVL) and methylentetrahydrofolate reductase (MTHFR C677T). Results: No mutations were reported in 36.1% in the control group, in 17.6% in the third group, in 15.8% in the second group and in 4.7% in the first group, thus obtaining a statistically significant difference only between the first and the control group for p<0.05 (Difference test, p=0.0008). Factor II heterozygous is registered in 23.5% in the first group, in 13.2% in the second group, in 5.9% in the third group and in 5.5.% in the control group. The percentage difference is statistically significant for p<0.05 between the first group versus third group and the first group versus control group (Difference test, p=0.0352, p=0.0269), the remaining percentage differences are insignificant. FVL heterozygous is registered with 23.5%in the first group, 10.5% in the second group, 20.6% in the third and 2.8% in the control group. The percentage difference is statistically significant for p<0.05 between the first group versus control group and the third group versus control group (Difference test, p=0.0084, p=0.0194), the remaining percentage differences are insignificant. Heterozygous mutations in the MTHFR C677T are present in 55.6% of the control group, in 52.9% of the third group, in 39.5% in the second group and in 34.9% of the first study group. MTHFR C677T homozygote is present in 48.8% in the first group, in 39.5% in the second, in 20.6% in the third and in 5.5% in the control group. Only one woman (2.6%) in the second group with infertility was factor II homozygous and two women (4.7%) in the first study group were FVL homozygous. Combined thrombophilic mutations are present in 32.6% of women in the first group, 21.1% in the second group, 17.6% in the third group and 5.6% in the fourth group, with statistically significant difference between the first and the control group for p<0.05 (Difference test, p=0.0030). The association between MTHFR homozygote and adverse pregnancy outcome and infertility for p<0.05 (Pearson Chi-square: 17.7865, p=0.000024, Pearson Chi-square: 12,0187, p=0.000526). There is a association between factor II heterozygote and adverse pregnancy outcome for p<0.05 (Pearson Chi-square: 4.7654, p=0.029036). Our study showed a significant association between MTHFR heterozygote in the first, second and third group compared to other mutations for p<0.05 (Pearson Chi-square: 20.9962, p=0.000000; Pearson Chi-square: 11.1815, p=0.000826; Pearson Chi-square: 4.6014, p=0.031946). There is statistically significant association between MTHFR homozygote in the first and second group compared to other mutations for p<0.05 (Pearson Chi-square: 6,9387, p=0.008435; Pearson Chi-square: 6,3921, p=0.008466). According to the cross-sectional relationship, MTHFR homozygous is a risk and increases the chance of adverse pregnancy outcome by six and a half fold (OR=6.5270) in the first group and increases the chance of infertility by approximately seven fold (OR=6.9000) in the second group. Conclusion: FVL heterozygous mutations is most common among women with adverse pregnancy outcome and IVF failure, factor II heterozygous among women with adverce pregnancy outcome and MTHFR homozygous in all three study groups. Evaluation and management of inherited thrombophilia may be beneficial for patients with adverse pregnancy outcome, infertility and IVF failure.
Inherited thrombophilia in adverse pregnancy outcome, infertility and in vitro fertilization failure
Докторска дисертација одбранета во 2020 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Розалинда Исјановска.
Keywords: inherited thrombophilia, adverse pregnancy outcome, infertility, in vitro fertilization failure